2022
DOI: 10.1111/jcmm.17652
|View full text |Cite
|
Sign up to set email alerts
|

Multiple machine learning methods aided virtual screening of NaV1.5 inhibitors

Abstract: Na v 1.5 sodium channels contribute to the generation of the rapid upstroke of the myocardial action potential and thereby play a central role in the excitability of myocardial cells. At present, the patch clamp method is the gold standard for ion channel inhibitor screening. However, this method has disadvantages such as high technical difficulty, high cost and low speed. In this study, novel machine learning models to screen chemical blockers were developed to overcome the above shorta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Ion channels represent a large membrane protein superfamily critical for physiological functions in both excitable and non-excitable cells. While patch-clamp electrophysiology remains the gold standard for screening ion channel inhibitors, this approach is associated with technical challenges, high costs, and slow throughput [ 165 ]. With the advancement of cryo-electron microscopy (cryo-EM) technology, the structures of ion channels are becoming increasingly elucidated.…”
Section: Application Of Ion Channel Therapy In MImentioning
confidence: 99%
“…Ion channels represent a large membrane protein superfamily critical for physiological functions in both excitable and non-excitable cells. While patch-clamp electrophysiology remains the gold standard for screening ion channel inhibitors, this approach is associated with technical challenges, high costs, and slow throughput [ 165 ]. With the advancement of cryo-electron microscopy (cryo-EM) technology, the structures of ion channels are becoming increasingly elucidated.…”
Section: Application Of Ion Channel Therapy In MImentioning
confidence: 99%
“…The ChEMBL database includes currently data for ~2.3 million ligands and ~15,000 targets, which were collected from published assays, scientific publications, or gathered from other databases and research institutions across the world [102,103]. Screening experiments on ion channels often exploit the ChEMBL ion channel dataset [104,105]. One can specify a particular ion channel family and subtype and obtain a list of small molecule ligands that are known to act on these targets.…”
Section: Virtual Ligand Libraries For Ion Channel Drug Discoverymentioning
confidence: 99%
“…Mostly ligand-based virtual screening approaches are aided with machine learning. For example, Kong et al [105] designed multiple machine learning frameworks based on ligand molecular fingerprints to screen the ChEMBL database to identify inhibitors of Na V 1.5 as potential anti-arrhythmic drugs.…”
Section: Prediction Of Ion Channel Ligands With Structure-based Virtu...mentioning
confidence: 99%
“…2 sodium channel inhibitors. 1,2,6,17,22,29,30,35,57 From 2018, more studies on VGSCs can be found in review articles. 24,37,40,43 However, these studies lack consideration of drug-target interaction networks, as well as comprehensive ADMET (absorption, distribution, metabolism, excretion, and toxicity) analysis.…”
Section: Introductionmentioning
confidence: 99%